Effect of mother's education on child's nutritional status in the slums of Nairobi - Abuya Benta A; Ciera James; Kimani-Murage Elizabeth (BMC, 2012)
Abstract Background Malnutrition continues to be a critical public health problem in sub-Saharan Africa. For example, in East Africa, 48 % of children under-five are stunted while 36 % are underweight. Poor health and poor nutrition are now more a characteristic of children living in the urban areas than of children in the rural areas. This is because the protective mechanism offered by the urban advantage in the past; that is, the health benefits that historically accrued to residents of cities as compared to residents in rural settings is being eroded due to increasing proportion of urban residents living in slum settings. This study sought to determine effect of mother's education on child nutritional status of children living in slum settings. Methods Data are from a maternal and child health project nested within the Nairobi Urban Health and Demographic Surveillance System (NUHDSS). The study involves 5156 children aged 0-42 months. Data on nutritional status used were collected between October 2009 and January 2010. We used binomial and multiple logistic regression to estimate the effect of education in the univariable and multivariable models respectively. Results Results show that close to 40 % of children in the study are stunted. Maternal education is a strong predictor of child stunting with some minimal attenuation of the association by other factors at maternal, household and community level. Other factors including at child level: child birth weight and gender; maternal level: marital status, parity, pregnancy intentions, and health seeking behaviour; and household level: social economic status are also independently significantly associated with stunting. Conclusion Overall, mothers' education persists as a strong predictor of child's nutritional status in urban slum settings, even after controlling for other factors. Given that stunting is a strong predictor of human capital, emphasis on girl-child education may contribute to breaking the poverty cycle in urban poor settings.